MANAJEMEN HATI SEBAGAI INTI PENDIDIKAN AKHLAK - Sudarto, Sudarto (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) Sekolah Tinggi Ilmu Tarbiyah Muhammadiyah Tempurrejo Ngawi, 2019)
Heart management that manages to manage the heart has the potential to positively develop a maximum of thinking and managing honestly its attitude becomes positive, and its negative potential is immediately detected and controlled so that it turns into a negative action. Mindfulness management solves itself, and then wants and is able to control itself after understanding who it really is. And the place to truly be who this is is in the heart, the heart that shows the character and you in front. . This heart management then gives birth to a principle that supports anyone who is clean, will be the center of all activities on earth. Moral education is part of the educational aspect of the Prophet who became the soul of Islamic education. Where experts discuss, that is the main purpose of education to educate morals and souls, instill a sense of fadhilah and prepare them in a holy life. In this case, Rosullullah himself became an inspiration for moral education. Regarding Heart Management as the Core of Moral Education, the heart is a place to ask. Rosul said: